Enhancing Policy Capacity in South Korea: integrating analytical, managerial, and political dimensions for effective governance - Kwangseon Hwang; Hyunseok Hwang (Cogent Social Sciences)
This paper examines the current state of Policy Capacity (PC) in South Korea, focusing on government officials and public researchers, and proposes strategies for enhancement. Despite significant progress, including the establishment of specialized agencies like the Korea Development Institute (KDI) and the National Research Council for Economics, Humanities, and Social Sciences (NRCS), challenges such as resource disparities between national and local governments, limited stakeholder engagement, and a reactive approach to policy analysis persist. The recent healthcare reforms proposed by President Yoon Suk Yeol, aimed at increasing annual medical school admissions, highlight both the strengths and weaknesses of the existing PC framework. This study emphasizes the need for clear mandates and coordination mechanisms, enhanced stakeholder engagement, and the leveraging of advanced data analytics and digital tools to improve policy outcomes. By adopting a comprehensive and adaptive approach to PC, South Korea can strengthen its ability to design and implement effective policies that respond to the evolving needs of its society. This holistic approach will ensure that policies are not only technically sound but also politically feasible and well-managed, fostering a more inclusive and effective governance system.